(untitled) (European Journal of Formal Sciences and Engineering, 2019)
With its formation, going back to thousands of years ago, ceramic is a material fact that the human beings obtain from earth for their emergency needs at first and by time for their different rituals and artistic requirements. Whether it is primitive or developed, ceramic formation requires energy and technology. And once ceramic is obtained, it resists time for thousands of years. Therefore, we have to be very selective when making ceramics. As ceramic artists, we always feel the breath of the tradition of thousands of years on our necks even if we want or not. Contemporary art trends show up one after another and disappear after a while. Meanwhile, “Is ceramic an art or a craft?” discussions are brought to agenda. Ceramic artists with a contemporary art education background may tend to keep up with the contemporary art trends because of the pressure caused by these discussions and the dominance of tradition. Among these art movements, Concept Art and Installation under its context still maintain their currency as the most long-lasting one in recent years. Concept is a most important part of the Conceptual Art Project. All materials or finished products that are created or will be created can be an expression tool for the artists. There is no limit here. However, knowing ceramic fact well can provide the ceramic artist with a chance to differentiate. For this reason, I believe that the ceramic artist’s concern should be creating ideas that underline being different in the context of ceramic. Using ceramics will be more meaningful if the ceramic object used in the artwork can not be replaced by another object and if the concept changes when the ceramic object is replaced... Ceramic object should challenge as follows: “This concept can be expressed only if I am used here. ” ….. Forcing ceramic artist to be more creative will prevent the artist from imitation of an ordinary concept art or installation and will add variety to concept art by creating remarkable difference. Surely, this requires a more powerful mind exercise. However, this is the only way ceramic and ceramic artist can accomplish their mission and underline the difference.